DATA-DRIVEN PERFORMANCE EVALUATION AS THE FOURTH PILLAR OF EDUCATIONAL HUMAN RESOURCE MANAGEMENT AT SD NEGERI KARANGREJO 01, SEMARANG - Juan Lestari Paiki; Tri Prasetyo Handayani; Fitria; Muji Astuti; Novia Indriani; Ngurah Ayu Nyoman Murniati (SOSIOEDUKASI, 2026)
Educational human resource management requires an integrated data-driven evaluation system to continuously enhance teacher capacity. This study aims to analyze the implementation of Data-Driven Performance Evaluation as the Fourth Pillar of Educational Human Resource Management at SD Negeri 01 Karangrejo, Semarang, focusing on its sensory, integrative, and motor functions, alongside its enabling and hindering factors. Employing a qualitative case study design, data were collected through non-participant observation, documentation, and semi-structured interviews with four informants (the principal and three teachers), and analyzed using thematic analysis. The findings reveal that while the sensory function is robustly institutionalized through digital platforms (e-Kinerja and Rumah Pendidikan) and the integrative function is enriched by organic, informal teacher reflections, the system suffers from "follow-up paralysis" due to a weak motor function that fails to link evaluation data to personalized professional development. Supportive principal leadership serves as the primary enabler, whereas heavy administrative burdens act as the main hindrance. Theoretically, this underscores the functional interdependence within the Five Pillars framework, while practically implying the urgent need for structured follow-up mechanisms and platform simplification to shift from mere administrative compliance to authentic professional growth.